310 ALBUMINURIA IN PRIMARY HYPERTENSION IS ASSOCIATED WITH TUBULOINTERSTITIAL INJURY EVEN IN SUBJECTS WITH NORMAL RENAL FUNCTION. (1st January 2006) - Singh, D.; Simoni, J.; Wesson, D. E.
Abstract : Purpose: Macroalbuminuria defined as urine albumin (mg) to creatinine (g) ratio (alb/cr) > 200 predicts subsequent GFR decline in primary hypertensives despite blood pressure reduction. Because hypertension-associated nephropathy consists of both glomerular and tubulointerstitial injury, we tested the hypothesis that primary hypertensives with macroalbuminuria but with normal GFR have renal tubulointerstitial injury. Methods: We recruited 281 subjects with primary hypertension and calculated GFR (Cockcroft Gault) > 90 mL/min but without diabetes mellitus or clinical evidence of vascular disease and compared them to 10 healthy, nonhypertensive, nondiabetic, controls with GFR > 90. Tubulointerstitial injury was determined as increased urine excretion of N-acetyl-b-D-glucosaminidase (NAGase), an enzyme released into urine in response to renal tubule epithelial injury. Results: Among recruited hypertensives were 218 subjects with normoalbuminuria (alb/cr < 20), 55 with microalbuminuria (alb/cr 20-200), and 8 with macroalbuminuria (alb/cr > 200). Urine NAGase excretion (mean 6 SE) expressed as units per g creatinine in an am spot specimen were not different between hypertensive subjects with normoalbuminuria and healthy controls (1.59 6 0.03 vs 1.58 6 0.27 U/g Cr, respectively, p = .97). By contrast, urine NAGase in hypertensives with microalbuminuria (1.83 6 0.086 U g/Cr) was higher than that for those with normoalbuminuria (p < .011, ANOVA). Furthermore, urine NAGase in hypertensives with macroalbuminuria (2.53 6 0.21 U/g Cr) was higher than in those with normoalbuminuria (p < .001) and microalbuminuria (p < .02, ANOVA). Conclusions: These data support the hypothesis that primary hypertensives with increased urine albumin excretion have renal tubulointerstitial injury compared to hypertensives with normal urine albumin excretion, even with normal GFR. These data suggest that hypertensives with macroalbuminuria have the greatest renal tubulointerstitial injury that might contribute to their greater risk for subsequent GFR decline.